The effects of agility type sprint interval training and continuous training on aerobic and anaerobic capabilities of young soccer players - Gahlul, S.; Cavar, M.; Hofmann, P. (Journal of Athletic Enhancement, 2017)
The study aimed to investigate the effects of short agility type (SIT) and continuous training (CT) to enhance aerobic and anaerobic capabilities in young soccer players. 34 participants from two teams were evaluated. The SIT group (n=17) performed three to five sets of 3 × 40 m agility type maximal sprints. The CT group (n=17) performed 28 to 41 min of continuous forward running at 65% HRmax. Both groups trained two sessions a week. The following Outcomes were measured at baseline and after 6 weeks: HRTP, HRmax, YOYOIR, 30 m sprint, 300 m shuttle run, vertical jump and agility test. At the post-test the 30 m time improved significantly in both the SIT and CT by 5% and 4.8%, agility test by 4.1% and 5.9%, Yo-YoIR test by 547 m and 501 m, respectively. SIT group recorded improvements in the 300 m shuttle run (3.7%) but CT showed a significant improvement in the HRTP. The 12 SIT training sessions showed no significantly greater effects on the soccer-specific aerobic and anaerobic capabilities in comparison to the CT training. Intermittent loads similar to SIT are frequently performed by soccer players with accompanying limited duration of experiment and volume most likely covered transformational specificity of applied SIT.